Are the Institute of Medicine guidelines for optimal gestational weight gain in twin pregnancies applicable to Japanese women?. Issue 1 (13th October 2020) - Shimura, Mai; Obata, Soichiro; Misumi, Toshihiro; Miyagi, Etsuko; Aoki, Shigeru
Abstract: Aims: To investigate whether the Institute of Medicine (IOM) guidelines for optimal gestational weight gain (GWG) in twin pregnancies are applicable to Japanese women. Methods: This was a retrospective study involving women who delivered full‐term twins at our tertiary center diagnosed with a normal prepregnancy body mass index. The women were divided into two groups, according to the optimal GWG recommended by the IOM (16.8–24.5 kg): the adequate GWG (AGWG) group with GWG meeting the guidelines and the low GWG (LGWG) group with GWG below the guidelines. Next, the women were divided into two groups according to birthweight: a group with both twins born appropriate for gestational age (AGA group) and a group with one or both twins born small for gestational age (SGA group). Their GWG as well as their pregnancy outcomes were compared. Results: A total of 265 women were included. The AGWG group had a significantly higher proportion of hypertensive disorders of pregnancy than the LGWG group. There was no significant difference in the proportion of women with both twins born AGA or the rate of admission to the neonatal intensive care unit. Meanwhile, the median GWG in the AGA group was 13.6 kg, which was significantly higher than 12.0 kg in the SGA group. And even the median GWG in the AGA group was below the lower limit of the IOM guidelines. Conclusion: The optimal GWG for Japanese women with twin pregnancies may be below the IOM guidelines.